SmartTourBabel: AI (Artificial Intelligence) Based Tourism System Development Model to Support Creative Economy and Sustainable Development in Bangka Belitung - Altiarika, Eka; Hikmawati, Agci; Fitriana, Fifin; Sari, Winda Purnama (Universitas Mohammad Husni Thamrin, 2025)
Tourism has long been recognized as an economic sector that can have a significant positive impact on economic and social development at the global level. The World Tourism Organization (UNWTO) notes that the global tourism sector has experienced a significant increase from year to year, contributing to national income and job creation. Tourism is an important sector that supports economic and social development, both globally, nationally and locally. In Indonesia, especially the Bangka Belitung Islands, this sector has great potential to support the creative economy and sustainable development. To maximize this potential, innovation is needed through Artificial Intelligence (AI) technology, especially in developing tourist destination recommendation systems. This research aims to develop an AI-based tourism system in Bangka Belitung by utilizing recommendation system technology and deep learning. This system is designed to provide a more personalized and relevant tourism experience for users by integrating tourism data and tourist habits. The research method used involves developing an AI model using a machine learning approach, which combines content-based and collaborative recommendations. It is hoped that the results of this research can produce a Flutter-based Android application that provides accurate tourist destination recommendations, improves service quality, and supports sustainable creative economic growth in Bangka Belitung. This research contributes to the application of AI technology in the tourism sector which can improve tourist experiences and support sustainable development.